Celtic myths - Collis, John
In ANTIQUITY a year ago, Vincent & Ruth Megaw found a useful parallel between the multiple definitions of the ancient Celts, as it can be seen from varied sources, and the several ways an individual's ethnic identity is seen and defined in the contemporary world. Here the other view is stated: that the methodology and interpretations advocated by the Megaws are both false and dangerous.